Dune : the graphic novel. Book 2, Muad'Dib - Herbert, Brian; Anderson, Kevin J., 1962- (Abrams ComicArts, 2022)
"In Dune: The Graphic Novel, Book 2: Muad'Dib, the second of three volumes adapting Frank Herbert's 1965 novel, Dune, young Paul Atreides and his mother, the Lady Jessica, find themselves stranded in the deep desert of Arrakis. Betrayed by their own physician, the treacherous Dr. Yueh, and destroyed by their greatest enemy, the Harkonnens, Paul and Jessica must find the mysterious Fremen or perish. As they continue to unravel the closely guarded secrets of the planet, they each face choices that will alter their fates--and their very lives--forever."--Page [2] of cover.